2016
DOI: 10.5455/amaj.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Zygomatic air cell defect - a brief review

Abstract: The aim of this paper was to analyst the literature published in the research related to zygomatic air cell defect. An internet search using keyword Zygomatic air cell defect was used to obtain details of the published literature in this research area from 1985 to 2016. The data available in the articles were analyzed in terms of ethnicity, prevalence, occurrence (unilateral/bilateral) and gender distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Carter et al [ 3 ]. observed an equal 1:1 ratio, while a systematic review conducted by Shetty et al [ 34 ]. noted that in most studies, a higher incidence rate of ZACD was observed in female study subjects when compared to their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Carter et al [ 3 ]. observed an equal 1:1 ratio, while a systematic review conducted by Shetty et al [ 34 ]. noted that in most studies, a higher incidence rate of ZACD was observed in female study subjects when compared to their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“… 1 The presence of air cells in the zygomatic extension of the temporal bone is referred to as a zygomatic air cell defect or a pneumatized articular tubercle (PAT). 2 PAT is defined as an asymptomatic radiolucent defect that does not extend beyond the zygomaticotemporal suture and is not associated with any bony growth or cortical destruction. However, it structurally weakens the roof of the glenoid fossa, resulting in a fragile temporomandibular joint (TMJ), 3 in which infections, tumors, or fractures may progress more easily.…”
Section: Introductionmentioning
confidence: 99%
“…Paranasal sinüslerde yaygınca görülen bu aksesuar hava hücreleri, kafatasında temporal kemik de dâhil olmak üzere birçok kemikte görülebilir [1]. Temporal kemiğin zigomatik uzantısında görülen hava hücrelerine Zigomatik Hava Hücresi Defekti veya PnömatizeArtikülerTüberkül (PAT) ismi verilir [2]. Bu hava hücreleri zigomatikotemporalsuturdan daha anteriora doğru uzantı göstermezler ve artikülereminens içerisinde yer alırlar [3].PATglenoidfossanın çatısında yapısal zayıflığa neden olaraktemporomandibular eklemin (TME) kırılgan bir hal almasına yol açabilir [4].…”
Section: Introductionunclassified